Inter-Rater Reliability and Downstream Financial Implications of Electrocardiography Screening in Young Athletes. Issue 8 (August 2017) - Dhutia, Harshil; Malhotra, Aneil; Yeo, Tee Joo; Ster, Irina Chis; Gabus, Vincent; Steriotis, Alexandros; Dores, Helder; Mellor, Greg; García-Corrales, Carmen; Ensam, Bode; Jayalapan, Viknesh; Ezzat, Vivienne Anne; et al.
Abstract : Background—: Preparticipation screening for cardiovascular disease in young athletes with electrocardiography is endorsed by the European Society of Cardiology and several major sporting organizations. One of the concerns of the ECG as a screening test in young athletes relates to the potential for variation in interpretation. We investigated the degree of variation in ECG interpretation in athletes and its financial impact among cardiologists of differing experience. Methods and Results—: Eight cardiologists (4 with experience in screening athletes) each reported 400 ECGs of consecutively screened young athletes according to the 2010 European Society of Cardiology recommendations, Seattle criteria, and refined criteria. Cohen κ coefficient was used to calculate interobserver reliability. Cardiologists proposed secondary investigations after ECG interpretation, the costs of which were based on the UK National Health Service tariffs. Inexperienced cardiologists were more likely to classify an ECG as abnormal compared with experienced cardiologists (odds ratio, 1.44; 95% confidence interval, 1.03–2.02). Modification of ECG interpretation criteria improved interobserver reliability for categorizing an ECG as abnormal from poor (2010 European Society of Cardiology recommendations; κ=0.15) to moderate (refined criteria; κ=0.41) among inexperienced cardiologists; however, interobserver reliability was moderate for all 3 criteria among experienced cardiologists (κ=0.40–0.53). Inexperienced cardiologists were more likely to refer athletes for further evaluation compared with experienced cardiologists (odds ratio, 4.74; 95% confidence interval, 3.50–6.43) with poorer interobserver reliability (κ=0.22 versus κ=0.47). Interobserver reliability for secondary investigations after ECG interpretation ranged from poor to fair among inexperienced cardiologists (κ=0.15–0.30) and fair to moderate among experienced cardiologists (κ=0.21–0.46). The cost of cardiovascular evaluation per athlete was $175 (95% confidence interval, $142–$228) and $101 (95% confidence interval, $83–$131) for inexperienced and experienced cardiologists, respectively. Conclusions—: Interpretation of the ECG in athletes and the resultant cascade of investigations are highly physician dependent even in experienced hands with important downstream financial implications, emphasizing the need for formal training and standardized diagnostic pathways. Abstract : Supplemental Digital Content is available in the text.